2019
DOI: 10.1016/j.seizure.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular disease burden in late-onset non-lesional focal epilepsy

Abstract: Late-onset non-lesional focal epilepsy, defined as new-onset seizures in patients older than 60 years, is diagnosed increasingly more often in relation to aging of the population. It has been attributed mainly to occult cerebral small vessel disease (SVD), although high levels of evidence to support this notion are lacking. This study aimed to evaluate the burden of leukoaraiosis, a marker of cerebral SVD, and hippocampal atrophy in patients with late-onset epilepsy (LOE). Methods: Brain magnetic resonance ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
(46 reference statements)
0
17
0
Order By: Relevance
“…Conversely, in a study focusing on lacunar strokes, hypercholesterolemia was not protective for seizures 19 . In a retrospective study comparing nonlesional LOE cases to controls, diabetes was more prevalent among patients with epilepsy, but no differences were noted for hypertension or dyslipidemia 20 . Smoking has been studied in the Nurses' Health study II among 116 608 women between the ages of 25–42, and it was found to be associated with an increased risk of seizures independent of stroke 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in a study focusing on lacunar strokes, hypercholesterolemia was not protective for seizures 19 . In a retrospective study comparing nonlesional LOE cases to controls, diabetes was more prevalent among patients with epilepsy, but no differences were noted for hypertension or dyslipidemia 20 . Smoking has been studied in the Nurses' Health study II among 116 608 women between the ages of 25–42, and it was found to be associated with an increased risk of seizures independent of stroke 21 …”
Section: Discussionmentioning
confidence: 99%
“…19 In a retrospective study comparing nonlesional LOE cases to controls, diabetes was more prevalent among patients with epilepsy, but no differences were noted for hypertension or dyslipidemia. 20 Smoking has been studied in the Nurses' Health study II among 116 608 women between the ages of 25-42, and it was found to be associated with an increased risk of seizures independent of stroke. 21 Recent, population-based, epidemiological studies have addressed the role of specific VRFs in the development of LOE also with conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between findings might be partly due to the use of semi-quantitative WML measures (Fazekas and Scheltens scales), which may be insufficiently robust for reliable statistical analysis by comparison with quantitative measures. The role of WMLs is however still debated [26]. Some radiological studies suggest that LOE is associated with lower cortical volumes [19].…”
Section: Discussionmentioning
confidence: 99%
“…So far, data on the association of this imaging marker with a late-onset epilepsy and interpretations of its meaning have been controversial ( 13 16 ).…”
Section: Introductionmentioning
confidence: 99%